Zur Lösemitteldiffusion in Polymernanoschichten: Schichtdicken- und Konzentrationsabhängigkeit - Buss, Felix (KIT Scientific Publishing, 2017)
Solution-casted polymer nanolayers are part of many technical applications. The solvent mass transport parameters are often unknown. However, they are a decisive factor for the determination of drying times, amounts of trace solvent, long-term stability and multilayer intermixing. By setting up a measurement system and conducting experimental and numerical investigations the difference in mass transport characteristics in micro- to nanoscale polymer layers is shown.